Islam dan Kearifan Lokal: Kajian Literatur tentang Relasi Budaya dan Agama di Indonesia - Purwoyuliyanto, Heru (Lembaga Yasin AlSys, 2025)
This study explores the relationship between Islam and local wisdom, focusing on the dynamics of interaction and mutual influence within the context of Indonesian culture. As a universal religion, Islam demonstrates a high degree of adaptability to local cultures, making it an integral part of the social life of communities. Conversely, local wisdom, which reflects traditional values and practices, often serves as a medium for introducing, reinforcing, and preserving Islamic teachings. This research employs the Systematic Literature Review (SLR) method to analyze a range of relevant literature concerning the relationship between Islam and local wisdom. The findings reveal that Islam is capable of acculturating with local culture without compromising its core values, thereby fostering harmony in social practices and religious traditions. Nevertheless, challenges persist in maintaining a balance between preserving local cultural heritage and upholding Islamic law in its pure form. The study affirms that the synergy between Islam and local wisdom plays a strategic role in strengthening national cultural identity, particularly amid rapid social change and globalization. In conclusion, an integrative and holistic approach is needed to address the complexities of the relationship between religion and culture in multicultural societies.